Spaces of capital/spaces of resistance: Mexico and the global political economy - Hesketh, Chris (2011)
Since 1994, Mexico has seen a proliferation of largely indigenous social movements asserting their right to land and territory, most notably within the southern part of the country. This thesis seeks to analyse why this has been the case by placing these movements within a theory of the production of space, and examining its role within the global political economy. It is submitted that events in southern Mexico can be explained as a clash between two distinct spatial projects; the spaces of capital on the one hand, and the spaces of resistance on the other. In order to make this argument, the inherent expansionary logic of capitalism as a mode of production is rendered, and it is detailed how the search for profit leads to constant alteration in socio-spatial relations. Using this framework, changes within the realm of production since the 1970s are investigated to reveal new socio-economic geographies, and the central role of class struggle in this process is asserted. The insertion of Latin America into global circuits of accumulation is then examined in relation to these arguments before the specific example of Mexico is turned to. Gramsci's concepts of passive revolution and hegemony are then deployed in order to analyse how spatial developments have been accomplished in Mexico though processes of state and class formation. Lastly, two regional case studies of the southern Mexican states of Oaxaca and Chiapas are explored in light of these theoretical contentions. These states serve to highlight not only the means by which capital is currently seeking to expand accumulation, but also underline the conflicts that arise from this process as new spaces of resistance have emerged that seeks to contest and remake space in radically new ways.